The Potential Role of Dopamine Pathways in the Pathophysiology of Depression: Current Advances and Future Aspects - Pannu, Arzoo; Goyal, Ramesh K. (CNS & Neurological Disorders - Drug Targets, 2025)
Depression is a serious mental health disorder that impacts more than 350 million individuals globally. While the roles of serotonin and norepinephrine in depression have been extensively studied, the importance of dopaminergic pathways—essential for mood, cognition, motor control, and endocrine function—often gets overlooked. This review focuses on four major dopamine (DA) circuits: the mesolimbic (MLP), mesocortical (MCP), nigrostriatal (NSP), and thalamic-tuberoinfundibular pathways (TTFP), and their roles in depression. The MLP, which is key to reward processing, is linked to anhedonia, a primary depression symptom. The MCP, projecting to the prefrontal cortex, affects cognitive issues like impaired attention and decision-making. The NSP, mainly responsible for motor control, is related to psychomotor retardation in depression, while the TTFP manages neuroendocrine responses, which are often disrupted in stress-related depressive conditions. Current antidepressant treatments mainly target serotonin and norepinephrine systems but tend to be less effective for patients with DArgic dysfunction, leading to treatment resistance. This review underscores emerging evidence that suggests targeting DArgic pathways could improve treatment outcomes, especially for symptoms like anhedonia and cognitive deficits that conventional therapies often fail to address. Future research should aim to combine advancements in neuroimaging, optogenetics, and genetic studies to better map DArgic pathways and create personalized treatment plans. This review highlights the potential for new therapies that focus on DA systems, which could pave the way for more effective and tailored approaches to treating depression.
Keywords: mesolimbic pathway